Posterior urethral valves: Risk factors for progression to renal failure. Issue 3 (June 2016) - Bilgutay, Aylin N.; Roth, David R.; Gonzales, Edmond T.; Janzen, Nicolette; Zhang, Wei; Koh, Chester J.; Gargollo, Patricio; Seth, Abhishek
Summary: Introduction: Posterior urethral valves (PUVs) are the most common etiology for congenital urethral obstruction and congenital bilateral renal obstruction. PUVs produce a spectrum of urologic and renal sequelae. Our aims were to assess outcomes of PUV patients, to determine whether vesicoureteral reflux (VUR) is a risk factor for progression to renal failure, and to identify other risk factors for poor outcomes. Materials and methods: We conducted a retrospective analysis of PUV patients from 2006 to 2014. Data collected included demographics, initial renal ultrasound (RUS) findings, creatinine at presentation and nadir, pre- and postoperative VUR status, presence or absence of recurrent urinary tract infections (UTIs), and surgical intervention(s). Univariate and multivariate analyses were used to determine risk factors for renal failure. Results: Of 104 patients, 42.3% (44/104) were diagnosed prenatally, 31.8% (14/44) of whom underwent prenatal intervention. Postnatally, 90.4% (94/104) initially underwent transurethral resection of PUVs (TUR-PUVs). Vesicostomy was the next most common index surgery (4.8%). Forty-two percent (44/104) required >1 surgery. The predominant second surgery was repeat TUR-PUV in 16 patients. At last follow-up (mean 28.8 months after initial surgery), 20.2% had chronic kidney disease (CKD) of at least stage IIIA, and 8.6% had progressed to end-stage renal disease (ESRD). Antenatal diagnosis, prematurity, abnormal renal cortex, and loss of corticomedullary differentiation (CMD) on initial RUS were associated with CKD and ESRD on univariate analysis, as were elevated creatinine on presentation and at nadir. Presence of pre- or postoperative VUR and recurrent UTIs were associated with the need for multiple surgeries, but not with poor renal outcomes. On multivariate analysis, nadir creatinine was the only independent predictor of final renal function. Conclusions: Our finding that creatinine is the only independent risk factor for poor renal outcomes in PUV patients is consistent with the literature. The effect of VUR has been controversial, and our finding that VUR is associated with need for multiple surgeries but not with CKD or ESRD is novel. Limitations include biases inherent to retrospective studies and relatively small sample size. The majority of patients with PUVs (56.7%) required one surgery and maintained renal function with CKD II or better (79.8%) up to 2 years after initial surgery. While multiple factors were associated with poor renal outcomes, nadir creatinine was the only independent predictor. VUR and recurrent UTIs were not associated with poor renal outcomes. Longer follow-up is necessary to identify risk factors for delayed progression of renal disease. Table Summary of results.   A. Predictors of ESRD p -value Categorical Prematurity 0.010 Prenatal diagnosis 0.034 Abnormal renal cortex on initial RUS 0.011 Loss of CMD on initial RUS <0.001 Continuous Presenting creatinine: mean non-ESRD pts vs ESRD pts: 1.3 vs 2.9 <0.001 Nadir creatinine: mean non-ESRD pts vs ESRD pts: 0.4 vs 2.7 <0.0001   B. Predictors of CKD p -value Categorical Prematurity 0.038 Prenatal diagnosis 0.014 Abnormal renal cortex on initial RUS <0.001 Loss of CMD on initial RUS <0.001 Continuous Presenting creatinine: mean non-ESRD pts vs ESRD pts: 1.3 vs 2.9 <0.0001 Nadir creatinine: mean non-ESRD pts vs ESRD pts: 0.4 vs 2.7 <0.0001   C. Predictors of >1 surgery p -value Categorical Prematurity 0.028 Prenatal diagnosis 0.027 Symptomatic presentation 0.048 Recurrent UTIs <0.001 Pre-op VUR 0.006 Post-op VUR 0.049 Loss of CMD <0.001 CKD, chronic kidney disease; CMD, corticomedullary differentiation; ESRD, end-stage renal disease; RUS, renal ultrasound; UTIs, urinary tract infections; VUR, vesicoureteral reflux.